2005
DOI: 10.2164/jandrol.04164
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Testosterone and Dihydrotestosterone Levels in Male Rat Accessory Sex Organs, Serum, and Seminal Fluid After Castration: Establishment of a New Highly Sensitive Simultaneous Androgen Measurement Method

Abstract: ABSTRACT:It is known that abnormal androgen dynamics in the tissues is a cause of androgen-dependent disorders. Investigation of tissue androgen levels could provide a clue to the elucidation of disorders. However, it is difficult to measure a trace amount of androgen in the tissues. We established a highly sensitive simultaneous quantification method of testosterone and dihydrotestosterone (DHT), which play the most important roles in the body among androgenic steroids in trace amounts, and investigated time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
37
1
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 29 publications
4
37
1
2
Order By: Relevance
“…Castration significantly decreased testosterone serum levels in normal and BDL male rats (Fig. 2B) (31). Similarly, administration of neutralizing antitestosterone antibody decreased testosterone serum levels in both normal and BDL male rats compared with rats treated with nonimmune serum (Fig.…”
Section: Expression Of Armentioning
confidence: 63%
“…Castration significantly decreased testosterone serum levels in normal and BDL male rats (Fig. 2B) (31). Similarly, administration of neutralizing antitestosterone antibody decreased testosterone serum levels in both normal and BDL male rats compared with rats treated with nonimmune serum (Fig.…”
Section: Expression Of Armentioning
confidence: 63%
“…We found that two weeks after gonadectomy, a condition that virtually implies absence of significant levels of circulating sex hormones (Kashiwagi et al, 2005), the amount of cell proliferation in the SVZ, evaluated 24 hours after the BrdU treatment, was significantly reduced in comparison to intact or sham-operated animals. Moreover, we found that a single injection of T restores in short time (24 hours) the level of cell proliferation.…”
Section: Discussionmentioning
confidence: 80%
“…Moreover, it is well established that sexual differentiation, growth and maintenance of the epididymis, ventral prostate and seminal vesicles are androgen-dependent processes (De-Krester et al, 1987;Dacheux et al, 1998;Tostain et al, 2004). It has been shown that a decrease in serum testosterone induced a decrease in secretory activity of the mass of the sexual tissues (Wilson, 1995;Kashiwagi et al, 2005). Accessory reproductive organs are structures rich in 5 alpha-reductase, an enzyme responsible for converting testosterone to dihydrotestosterone is the active hormone (Johnson and Everitt, 2002).…”
Section: Discussionmentioning
confidence: 99%